2016
DOI: 10.1007/s10973-016-5611-7
|View full text |Cite
|
Sign up to set email alerts
|

Furniture wood waste as a potential renewable energy source

Abstract: In this study, the combustion behavior of raw waste wood from furniture and samples torrefied at temperatures of 473, 513, 553 and 593 K was investigated. TG-DTG analysis showed that the mass loss in the first stage of the process decreased with the temperature of torrefaction, whereas the temperature in the second stage increased. The influence of torrefaction and combustion parameters on greenhouse gas emissions were investigated by the FTIR technique. The characteristic combustion parameters were also deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…4, one can clearly see the emission of the same volatile decomposition products under the first decomposition stage (T max1 ) as compared to those observed for the starch-gpoly(phenyl acrylate) copolymers. This was confirmed by the presence of the following bands on the FTIR spectra gathered at T max1 which were responsible for the following inorganic species: CO 2 (at 670 and 2330-2365 cm [39][40][41]) has been indicated. It confirmed that the decomposition mechanism of starch-g-copolymers under the first decomposition stage was independent on the type of aromatic acrylate monomer used for the grafting process.…”
Section: Tg-ftirmentioning
confidence: 79%
“…4, one can clearly see the emission of the same volatile decomposition products under the first decomposition stage (T max1 ) as compared to those observed for the starch-gpoly(phenyl acrylate) copolymers. This was confirmed by the presence of the following bands on the FTIR spectra gathered at T max1 which were responsible for the following inorganic species: CO 2 (at 670 and 2330-2365 cm [39][40][41]) has been indicated. It confirmed that the decomposition mechanism of starch-g-copolymers under the first decomposition stage was independent on the type of aromatic acrylate monomer used for the grafting process.…”
Section: Tg-ftirmentioning
confidence: 79%
“…The cyclization and charring reactions are also indicated by an increase of nearly 174% in the residue after thermal decomposition of OSB relative to beech wood and by more than 200% relative to pellets. The thermal decomposition residue of MDF is 138% greater than that of beech wood and over 160% greater than that of pellets [30].…”
Section: Thermal Analysis Of Wood and Wood-based Materialsmentioning
confidence: 90%
“…Method of quantitative and qualitative analysis of toxic gaseous products, in detail was described in previous authors publication [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen, the initial mass loss starts at almost the temperature up to 100°C which can be attributed to moisture, with an approximately corresponding mass loss of 5.70%. 43 This is followed by a great weight loss where the decomposition of rice husk sawdust biomass and Rh-B takes place with maximum rate between 250°C and 375°C. In this degradation stage, the weight loss is by reason of the thermal decomposition of the wood component: hemicelluloses are degraded mainly between 200°C and 300°C, cellulose in the range of 275-400°C, and lignin in 250-500°C.…”
Section: Thermal Analysismentioning
confidence: 99%